Putusan mahkamah konstitusi no 46/puu-viii/2010 yang kontradiktif dengan hukum islam ; analisis kasus machica muchtar - Romadhona, Aisyah (Maliki Interdisciplinary Journal, 2025)
Efforts to obtain good offspring must be based on good methods. Islam has regulated various laws regarding how to have a good marriage, how to obtain quality offspring, and how to properly glorify offspring. Islam has regulated it in detail. However, not all countries with Muslim populations, even those with a majority Muslim population, agree to implement their government regulations with Islamic law. As Indonesia is the country with the second largest Muslim population in the world, reaching 87.2% of the total population. But the Indonesian government and its population consciously declare that Indonesia is a rule of law country with the ideology of Pancasila. Apart from that, Indonesia provides privileges to its Muslim population by enacting laws which so far are in harmony with Islamic law. Until 2012, on February 27 in an open courtroom, the Constitutional Court issued final decision No. 46/PUU-VIII/2010.This decision regarding the Machica Muchtar case will be a decision that is contradictory to Islamic law and is widely debated by legal experts in Indonesia.